Hidrólise subcrítica de palha e cascas de arroz para obtenção integrada de açúcares fermentescíveis e material adsorvente - Abaide, Ederson Rossi (2019)
In this research, coproducts from rice harvesting and manufacturing, such as straw and husks, were submitted to subcritical water hydrolysis in order to obtain a hydrolyzed liquid containing fermentable sugars and a solid residue with an adsorption capacity higher than the fresh biomass. The assays were carried out at a laboratory-scale unit containing 50 mL hydrolysis reactor heated by thermal resistance, preheating baths, temperature sensors and controllers, pressure gauges, and pressure/flow control valves. The following process variables were studied: temperature (180, 220 and 260°C) and water / solids mass ratio (7.5 and 15 g water/g initial biomass). The pressure was set at 25 MPa and the total reaction time was defined as 15 minutes. Some responses were analyzed in order to identify the best process condition: reducing sugar (RS) yield, compositions of fermentable sugars and inhibitors, modification in the morphology and surface area of the hydrolyzed biomass, and residual adsorption capacity. In the experimental assays with rice straw, the highest RS yield of 33.4 ± 4.3 g/100 g rice straw (dry basis) was obtained at 220°C and water / solids mass ratio of 7.5 g water/g initial biomass (220°C / R-7.5; it corresponds to the flow rate of 10 mL/min). For rice husks, the best yield of RS was 18.3 ± 2.3 g/100 g of rice husks (dry basis) in the condition of 220 °C / R-7.5. The analysis of the hydrolyzed medium by high performance liquid chromatography indicated the presence of arabinose, cellobiose, glucose and xylose, and also inhibitors such as furfural and hydroxymethylfufural. When the surface area for the hydrolyzed rice straw was evaluated, the best condition was 260°C / R-7.5, with a surface area of 10.60 m2/g. For rice husks, the highest surface area was 24.24 m2/g for the same condition: 260°C / R-7.5. The rice straw submitted to subcritical water hydrolysis at 180°C / R-7.5 (g water / g initial biomass) presented the highest adsorption capacity of 2-nitrophenol at pH 7 (92.97 ± 1.31 mg/g).